2017
DOI: 10.1177/0890117117694287
|View full text |Cite
|
Sign up to set email alerts
|

Development, Implementation, and Evaluation of Active Lions: A Campaign to Promote Active Travel to a University Campus

Abstract: This multistrategy approach to increase active transportation on a college campus provided insight on the process of developing and implementing a campaign with the potential for impacting health behaviors among campus members.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 47 publications
1
45
0
1
Order By: Relevance
“…In this respect, we demonstrate that a smartphone app can be used as a means of intervention, despite the fact that we observed similar difficulties to previous studies, such as a rather low rate of participants’ enrollment and substantial drop out of participants from the study, e.g., [ 8 , 26 , 27 ].…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…In this respect, we demonstrate that a smartphone app can be used as a means of intervention, despite the fact that we observed similar difficulties to previous studies, such as a rather low rate of participants’ enrollment and substantial drop out of participants from the study, e.g., [ 8 , 26 , 27 ].…”
Section: Discussionsupporting
confidence: 64%
“…Practical examples of these developments include Bopp et al [ 8 ] combining TTM and social cognitive theory targeting behavioral constructs of self-efficacy, self-regulation, outcome expectations, and processes of change. Thigpen et al [ 3 ], using the Model of Action Phases, found that travel attitudes matter more to progression toward regular commuter cycling than travel attributes, thus tentatively supporting the efficacy of soft policies focused on changing travel attitudes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of active transportation, smartphones can be used to provide real-time measures of travel behaviour and deliver a behaviour change intervention. One previous study used a smartphone app to promote active transport at a university campus; however, it was part of a multi-strategy campaign, thus, the effect of the app itself could not be evaluated [ 19 , 20 ]. To the best of our knowledge no study has evaluated whether a smartphone application (app) can promote active transportation.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has outlined how social media can be used in health promotion efforts and communication for health-related programming, though reach and outcomes are still unclear ( 28 , 29 ). A recent campaign to promote active travel at a large university used social media extensively and saw widespread reach and an increased likelihood of active travel among those who had been exposed to the social media efforts ( 30 , 31 ). This indicates that social media may be evolving to become among the more far-reaching forms of communication in biking-related initiatives.…”
Section: Discussionmentioning
confidence: 99%